IoT-Based Battery Monitoring System for Lithium-Ion using Fuzzy Logic Method - Ardika Bagus Saputra; Isa Hafidz; Susijanto Tri Rasmana (Journal of Computer Electronic and Telecommunication, 2025)
The increasing number of vehicles in Indonesia has a negative impact if it is allowed to continue; one solution is to switch to environmentally friendly electric vehicles. One of the main components of electric vehicles is the battery. IoT-based battery monitoring is needed to check battery health using the fuzzy logic method with LED notification results. Notifications indicate whether the battery is in a safe, alert or dangerous condition. The results of battery monitoring in a discharge condition with a load of battery voltage decrease linearly compared to temperature, which changes according to the ambient temperature. In a charging condition, the battery voltage increases linearly, and the peak temperature is higher than when discharged with a load. When testing a load variation of 4 LEDs, the voltage decreases faster, and the temperature rises higher than with a load of 2 LEDs. With these various conditions, the application of fuzzy logic is used to monitor the condition of the battery in a discharge or charge state. This study aims to develop IoT-based battery monitoring by implementing the use of fuzzy logic as a battery notification when the battery is in a safe, alert, or dangerous state. This battery monitoring system can monitor the battery in real time and is quite accurate by using IoT, which can facilitate battery monitoring.